RGB Color Model: Effect of Color Change on a User in a VR Art Gallery Using Polygraph - Drofova, Irena; Richard, Paul; Fajkus, Martin; Valasek, Pavel; Sehnalek, Stanislav; Adamek, Milan (Sensors (Basel, Switzerland), 2024)
This paper presents computer and color vision research focusing on human color perception in VR environments. A VR art gallery with digital twins of original artworks is created for this experiment. In this research, the field of colorimetry and the application of the L*a*b* and RGB color models are applied. The inter-relationships of the two color models are applied to create a color modification of the VR art gallery environment using C# Script procedures. This color-edited VR environment works with a smooth change in color tone in a given time interval. At the same time, a sudden change in the color of the RGB environment is defined in this interval. This experiment aims to record a user's reaction embedded in a VR environment and the effect of color changes on human perception in a VR environment. This research uses lie detector sensors that record the physiological changes of the user embedded in VR. Five sensors are used to record the signal. An experiment on the influence of the user's color perception in a VR environment using lie detector sensors has never been conducted. This research defines the basic methodology for analyzing and evaluating the recorded signals from the lie detector. The presented text thus provides a basis for further research in the field of colors and human color vision in a VR environment and lays an objective basis for use in many scientific and commercial areas.
Keywords: artwork; signals; 3D model; virtual reality; polygraph; art gallery; lie detector; sensors; digital twins; art digitization; color model; gamut